A Scoping Review of Positive Psychology Studies on Widowed Older Women - Mulyani, Made; Lestari, Made Diah; Hartijasti, Yanki; Han, Donghee (Faculty of Psychology Universitas Gadjah Mada, 2025)
Previous studies on older widows have focused on the negative aspects of spousal loss, such as loneliness, anxiety, and depression, positioning them as vulnerable groups. This perspective tends to overlook the potential of older widows in achieving successful aging. This study aimed to map the concepts within the scope of positive psychology that have been applied in research on older widows, and to explore how these approaches can support healthy and successful aging. A literature search was conducted on Google Scholar, covering publications from 2016 to 2025. A total of 9,480 articles were identified and screened based on predetermined inclusion and exclusion criteria. After reviewing abstracts and full texts, eight articles were included in this scoping review. There is a consistent pattern: older widows can achieve successful aging through positive psychology and spirituality. However, several contradictions between concepts were found, particularly regarding the sources of emotional resilience, between external social support and internal spiritual strength. Views on the meaning of life also vary, rooted in past achievements and acceptance of painful experiences and present hopes. Adaptation is described through both active (autoplastic adaptation) and passive (surrender to fate) approaches. Optimism is often considered a universal strength, but it has not been widely studied in the context of the socioeconomic limitations faced by older widows. The integration of intrapersonal aspects, e.g., resilience, meaning in life, well-being, and optimism, along with social and spiritual dimensions, including social support and spirituality, contributes to helping older widows achieve successful aging.